Anemia en población infantil: Características clínicas y de laboratorio. - Chávez Orozco, Evelin Yajaira (2025)
Anemia is a global problem that affects a large number of children. Therefore, these alterations can trigger other diseases in the future, putting health at risk. The objective of anemia is to collect information on anemia referring to the child population, clinical characterization, and laboratory tests. It was a descriptive investigation because it is a bibliographic work in which it was essential to collect updated data about the research variables according to the design. It was a documentary work based on reviewing and analyzing books, thesis, and scientific articles published on academic research platforms such as Scielo, Pubmed, Science Direct, Springer, Medigraphic Elsevier, and Google Scholar. The search presents a temporal and chronological sequence of a transversal and retrospective type carried out in a specific period. The population consisted of 39 bibliographic sources, the topic to be studied being a publication period between 2019 and 2024. The researchers used these articles due to their importance in the content investigated. According to the documents analyzed, among the predominant factors for childhood anemia, nonbreastfeeding, low weight/height, place of origin, and malnutrition were present, and its most relevant symptoms were jaundice, fever, and diarrhea. Childhood anemia is common in countries where the poverty rate and malnutrition are prominent; therefore, it is necessary to provide medical attention to vulnerable groups.